Answer:
b=3.54
Step-by-step explanation:
9.89-6.35=3.54
The answer is 5 and -5, because squaring a positive or negative number give the same value, so square rooting that number should give back those positive and negative value. THIS ONLY WORKS FOR WHEN THE SQUARE ROOT OR THE SQUARING IS AN EVEN NUMBER.
y = x^2 + 5x -3
y-x =2
Replace y in the second equation with the first one:
x^2 + 5x -3 - x = 2
Simplify by combining like terms:
x^2 + 4x -3 = 2
Subtract 2 from both sides:
x^2 + 4x -5 = 0
Fctor the polynomial:
(x-1) (x+5) = 0
Solve for both X's:
x = 1 and x = -5
Now replace x in the second equation with both value and solve for y:
y -1 =2, y = 3
y - -5 =2, y +5 = 2, y = -3
Now combine the sets of answers:
(1,3) and (-5,-3)
Answer:
8780.
Step-by-step explanation:
-6 times -6 is 36 + 8744